The family as provider of intergenerational support during COVID-19: a study into the mental health consequences for 65+ Europeans - Lore Van Herreweghe; Wim Van Lancker (Frontiers Media S.A., 2024)
IntroductionIntergenerational support is an important determinant of mental health. Due to limited access to formal care, the role of the family as provider of support became more prominent during the COVID-19 pandemic. To date, it remains unclear how intergenerational support from adult children to older parents was affected during the pandemic and whether this had consequences for the mental health of the parent generation.MethodsUsing data from the Survey of Health, Ageing and Retirement in Europe (SHARE) Corona Surveys, we explore whether changes in support going from non-coresident adult children to their parents are associated with parents' increase in depressive feelings. Additionally, we test whether the pandemic context and public health measures affected this relationship.ResultsDuring the pandemic, families are found to provide more support. These changes in intergenerational support, however, were related to increased depressive feelings for the older parents. Furthermore, both the strictness of public health measures and the concurrent epidemiological situation affected this relationship.ConclusionWe conclude that the family is an essential source of late-life well-being, but stressful life events, such as public health crises, put pressure on these intergenerational relations with potential adverse mental health outcomes. Future policies should take into account the ambivalent nature of intergenerational relationships.